Ploidy, Fertility, and Phenotypes of F1 Hybrids between Tetraploid Highbush Blueberry Cultivars and Diploid Vaccinium elliottii - Elliot H. Norden; Paul M. Lyrene; Jose X. Chaparro (HortScience, 2020)
A progeny of 55 blueberry seedlings produced by pollinating 4301 flowers of tetraploid highbush blueberry cultivars with pollen from 19 different diploid Vaccinium elliottii plants was studied to determine hybridity and ploidy. Of the 21 seedlings whose phenotypes were intermediate between parental types, indicating hybridity, 18 were triploid and three were tetraploid. Pollen of the triploids, when viewed at ×250, was almost all shrunken and aborted, although some triploid hybrids produced a few large, plump microspores in dyads or monads. Triploids produced no seed when pollinated with pollen from 4x highbush or 2x V. elliottii or when open-pollinated outside the greenhouse in the presence of fertile diploid and tetraploid blueberries. Tetraploid hybrids produced large populations of vigorous seedlings when intercrossed. Both triploid and tetraploid F1 hybrids were intermediate between the parents in leaf size and flower size. The triploids produced no berries; the tetraploids were intermediate between the parents in berry size but averaged lower in Brix and berry firmness than either parent. Seven additional F1 hybrids from reciprocal crosses were obtained by pollinating 2309 flowers of 2x V. elliottii with pollen from tetraploid highbush cultivars. Although five V. elliottii clones served as female parents in these crosses, only one produced any seedlings. Six of the seven hybrids flowered and were fertile tetraploids; one was a sterile triploid.